Estrategia trófica de Oreochromis spp. (Actinopterygii: Cichlidae) del lago de Cuitzeo, Michoacán, México - Martínez Morales, Pedro de Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
Introducing species is a major cause of biological extinction of species. In Mexico fishes have been introduced which are considered as threats to freshwater systems. Such as Oreochromis spp (known as tilapia or bream) introduced into lake of Cuitzeo since the early 1970's. The tilapia can cause changes in the biological structure of a community of a lake. However, it is not possible to establish whether there is damage and what is the magnitude of this without understanding the role that Oreochromis spp plays. In the present study we aim to establish the trophic strategy of Oreochromis spp in Lake Cuitzeo as well as the spatio-temporal variation by the analysis of stomach contents. Sampling was performed on five sites of the lake during an annual cycle. The results suggest that Oreochromis spp. is an omnivorous, with changes in the diet with increasing size and operates in specific trophic guilds: zoo planctovorous when the size is less than 29 mm and detritivorous when size exceeds 51 mm. According to the IRI it was possible to establish the most consumed food items: cladocerans, copepods, debris and plant debris. Additionally the physicochemical conditions of the sites against the diet of different sizes were analyzed. The results allow us to understand the trophic role of Oreochromis spp within the biological community in Lake Cuitzeo and also provide the basis for further investigations of interspecific competition among other fish.

Los efectos de la introducción de especies invasoras son una de las principales causas de extinción biológica. En México se han introducido peces que se consideran una amenaza para los sistemas dulceacuícolas, como por ejemplo Oreochromis spp (conocida como tilapia o mojarra). Fue introducida en el lago de Cuitzeo desde la década de los 1970’s. La tilapia puede ocasionar modificaciones en la estructura de la comunidad biológica del lago. En el presente trabajo se tiene como objetivo establecer la estrategia trófica de Oreochromis spp del lago de Cuitzeo y su variación espacio-temporal, por medio del análisis de contenido estomacal. Se realizaron recolectas en cinco sitios en el lago durante un ciclo anual. Los resultados sugieren que Oreochromis spp. es un organismo que cambia su dieta a medida que aumenta de talla y opera en gremios tróficos específicos: es zooplanctófago cuando su talla es menor a 29 mm y herbívoros detritófago cuando su talla rebasa 51 mm. De acuerdo con el Índice de Importancia Relativa (IIR) fue posible establecer los artículos alimenticios más consumidos: cladóceros, copépodos, detritos y restos vegetales. Por otro lado, se analizaron las condiciones fisicoquímicas de los sitios contra la dieta de las diferentes tallas y aparentemente se ven afectados los alevines. Los resultados nos permiten comprender el papel trófico de Oreochromis spp dentro de la comunidad biológica en el lago Cuitzeo, además proporcionan las bases para posteriores investigaciones de competencia interespecífica entre otras.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2016-0441; Contenido estomacal; Mojarra; Variación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1751